The relation between GAD1 and PTSD symptoms: Shared risk for depressive symptoms. (December 2017) - Bountress, Kaitlin; Sheerin, Christina; Amstadter, Ananda B.; Mandel, Howard; Voltin, Joshua; Wang, Zhewu
Abstract : Highlights: A genetic risk sum score capturing risk for GAD1 predicted PTSD symptoms. The same score was associated with depressive symptoms. These findings held over and above age, gender, and ethnicity.